Effects of swim training on liver carcinogenesis in male Wistar rats fed a low-fat or high-fat diet - Aguiar e Silva, Marco Aurelio [UNESP]; Vechetti-Junior, Ivan Jose [UNESP]; do Nascimento, Andre Ferreira [UNESP]; Furtado, Kelly Silva [UNESP]; Azevedo, Luciana; Ribeiro, Daniel Araki; Barbisan, Luis Fernando [UNESP] (Canadian Science Publishing, Nrc Research Press, 2012)
The present study aimed to investigate the beneficial effects of swim training on the promotion-progression stages of rat liver carcinogenesis. Male Wistar rats were submitted to chemically induced liver carcinogenesis and allocated into 4 major groups, according their dietary regimen (16 weeks) and swim training of 5 days per week (8 weeks): 2 groups were fed low-fat diet (LFD, 6% fat) and trained or not trained and 2 groups were fed high-fat diet (HFD, 21% fat) and trained or not trained. At week 20, the animals were killed and liver samples were processed for histological analyses; immunohistochemical detection of persistent or remodeling preneoplastic lesions (pPNL and rPNL) expressing placental glutathione S-transferase (GST-P) enzyme; or proliferating cell nuclear antigen (PCNA), cleaved caspase-3, and bcl-2 protein levels by Western blotting or malonaldehyde (MDA) and total glutathione detection by HPLC. Overall analysis indicated that swim training reduced the body weight and body fat in both LFD and HFD groups, normalized total cholesterol levels in the HFD group while decreased the MDA levels, increased glutathione levels and both number of GST-P-positive pPNL and hepatocellular adenomas in LFD group. Also, a favorable balance in PCNA, cleaved caspase-3, and bcl-2 levels was detected in the liver from the LFD-trained group in relation to LFD-untrained group. The findings of this study indicate that the swim training protocol as a result of exercise postconditioning may attenuate liver carcinogenesis under an adequate dietary regimen with lowered fat intake.
Keywords: swim training; rat liver carcinogenesis; high-fat diet; preneoplastic-neoplastic lesions